Penatalaksanaan Perawatan Hiperpigmentasi Pada Gingiva Dengan Metode Scrapping Menggunakan Pisau Bedah: Studi Kasus - Nita Nurniza; Ina Hendiani; Yanti Rusyanti; Agus Susanto (Majalah Sainstekes, 2018)
Hyperpigmentation is a disorder of the gingiva caused by various factors including heredity, disease, drugs, smoking habits. This can occur because of the accumulation of melanin pigment in the basal gingival layer resulting in a brownish or blackish color on the surface of the gingiva which when viewed aesthetically is not good because it is not like the normal gingival color of coral pink. Objective: to get the gingival color back to normal, namely coral pink. Management in cases of pigmentation using the surgical method by scrapping using a scalpel No.15. In this study there were 3 cases, namely, case 1, a 20-year-old female patient had genetic or genetic hyperpigmentation. Case 2, a 27-year-old male patient had genetic or genetic hyperpigmentation. Case 3, a 24-year-old female patient had gingival pigmentation due to smoking habits. The results of surgical management in all three cases, namely the gingival depigmentation method by scrapping gave a good esetetic result, but for gingival hyperpigmentation in cases 1 and 2 it could recur later.